Numerical Simulation and Experimental Research on Indoor Environment Separated with Down-Feed Air Curtain - 郭春梅 张于峰 常茹 王晓东 (Transactions of Tianjin University, 2009)
Indoor environment separated with down-feed air curtain was numerically simulated and experimentally researched. Indoor airflow and temperature fields separated with air curtain were numerically simulated. Results show that both polluted airflow and thermal air current can be separated with a down-feed air curtain to prevent contaminants from spreading in the room space. In a test chamber, the smoke of burning Tibetan incense served as the source of contaminants, and the probe test shows that 1.0 μm is the prevailing diameter of the smoke particles. During the release of the smoke, the particle concentration of the indoor air was tested with a laser particle counter at the points of three different heights from the floor when the air curtain was running or not. Experimental results show that the higher the test point is located, the lower the particle concentration is, implying that the separating or isolating effect decreases as the air velocity of the curtain reduces along with the height descends. According to both simulation and experimental results, down-feed air curtain can separate indoor environment effectively when the supply air velocity of air curtain is not less than 3 m/s. In order to strengthen separation effect, it is suggested that the supply air velocity be speeded up to 5 m/s.